Assessing the major rework factors in transport infrastructure projects in Malaysia - Lim, Ing Rhong (2022)
Development of transport infrastructure projects (TIP) is pivotal as it inaugurates national connectivity and accessibility, also establishes impetus towards the blossoming of the local economies. However, rework seems to be the ubiquitous issue and a deep-rooted dilemma that imperil the TIP’s growth and performance. There is substantial lack of attention by the Malaysian construction industry and severe paucity of extant studies investigated into the rework factors of TIP. Thus, this research aims to bridge the knowledge gap by identifying the major rework factors; evaluating the criticality of the major rework factors; and appraising the rework reduction measures within the context of Malaysian TIP. Through a comprehensive literature review, assessment had been accomplished where 40 rework factors and 15 rework reduction measures had been identified. Meanwhile, 108 questionnaire responses were being collected from various industry personnel including client, consultant and contractor. The Importance Index technique shown the five significant factors that provoke reworks are poor communication; noncompliance of task requirements; inappropriate construction method; lack of scope clarity and lack adherence to quality assurance. Furthermore, five underlying factors have been unveiled through factor analysis, namely, inadequacy in construction stage considerations; incompetency of site practitioners; inadequacy in feasibility stage considerations; inappropriate allocation of resources and haphazard information delivery system. Meanwhile, the five most significant reduction measures via Relative Importance Index approach are maintaining effective communication; client’s needs and priorities should always be clear; accurate contract documentation and design; implementing constructability strategy and utilising BIM tools. Lastly, the statistical relationship between the factors and potential measures were examined via correlation test. The five most effective and practical measures for the addressed factors are workers should undergo proper training programmes; maintaining effective communication; be conscious and responsive of site conditions; implementing constructability strategy and ensure skilled workforce in carrying out special tasks. Conclusively, this research assessment could be the basis for Malaysian researchers to look into its implication in the near future while the proposed potential measures should be further investigated to maximise the development of Malaysian TIP.